Dynamic Assessment for Identification of Twice-Exceptional Learners Exhibiting Mathematical Giftedness and Specific Learning Disabilities. Issue 2 (3rd April 2019) - Al-Hroub, Anies; Whitebread, David
Abstract : The purpose of this research was to investigate the utility of dynamic assessment (DA) in identifying a group of twice-exceptional students who exhibited mathematical giftedness and specific learning disabilities (MG/LDs). A quantitative method was applied by a multidisciplinary team to identify 30 students (16 girls and 14 boys) in the fifth and sixth grades, aged 10 years to 11 years 11 months, at three public elementary schools in Amman, Jordan. The findings of the dynamic mathematics assessment showed (a) a high variance in performance between the pre- and posttests and (b) a lack of relation with conventional static assessment (e.g., mathematics achievement tests and the arithmetic subtest in the Wechsler Intelligence Scale for Children, Jordanian version). DA was found to be beneficial for elementary school boys and girls and to affect their mathematics achievement to the same extent. No group differences were observed between low and high achievers in their learning potential as revealed by their performance on DA.